Endothelial dysfunction and periodontal hemodynamic disturbances in young patients with nicotine dependence - A. V. Naumov (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To investigate the association between periodontal hemodynamic disturbances and systemic endothelial dysfunction (ED); to assess the effectiveness of various toothpastes for periodontal disease prevention in patients with nicotine dependence. Material and methods. In total, 120 young individuals aged 22—28 years were divided into 2 groups, according to the presence or absence of nicotine dependence. All participants underwent ED assessment with the EndoPAT device. Microcirculation (MC) was assessed with the high-frequency Doppler ultrasound system MinimaxDoppler-K. Patients with nicotine dependence were divided into 2 subgroups. Subgroup A was recommended to use the R.O.C.S. toothpaste Anti-Tobacco (WDS Laboratories) twice a day, while Subgroup B participants were recommended to use the toothpaste Colgate Advanced Whitening with polishing micro-crystals (ColgatePalmolive Poland) twice a day. Results. Significant between-group differences were observed for reactive hyperemia index and augmentation index. ED severity was higher in smoking participants. Velocity and volume parameters of periodontal MC were lower in smokers. The use of each specialized toothpaste was associated with improved periodontal MC, decreased prevalence of periodontal pathology-related complaints, reduced periodontal pocket depth, and decreased periodontal index values; however, the Anti-Tobacco toothpaste was more effective. Conclusion. Young smokers demonstrated а more severe ED and disturbed periodontal MC, which manifested in a more advanced periodontal disease.